MEMPERKUAT KEBERLANJUTAN MASYARAKAT DESA SIRNA JAYA, BOGOR: PELATIHAN KESIAGAAN BENCANA UNTUK KELOMPOK POKDARWIS RAWA GEDE - Ahmad Tijari; Hafid Abbas; Jaenal Mutakim (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Disaster preparedness training in Sirna Jaya Village is important to protect the community from the negative impacts of disasters. In this training, participants learn first aid and risk reduction through different types of disasters. This disaster first aid training involves expert lecture sessions, experience-sharing discussions, focus group discussions, and disaster simulations. After the training, weekly monthly monitoring and evaluation were conducted through interviews, group discussions, and direct observation. Evaluation data is used to evaluate programs and provide recommendations for the development of similar programs in the future. The evaluation results showed positive changes in individual and group preparedness, proving the effectiveness of this training. This training increases knowledge and builds the foundation of resilient and disaster-ready communities.